2020
DOI: 10.1111/exd.14069
|View full text |Cite
|
Sign up to set email alerts
|

High bacterial colonization and lipase activity in microcomedones

Abstract: Background:Although acne vulgaris has a multifactorial aetiology, comedogenesis and bacteria colonization of the pilosebaceous unit are known to play a major role in the onset of inflammatory acne lesions. However, many aspects remain poorly understood such as where and when is the early stage of the Propionibacterium acnes colonization in follicular unit? Our research aimed at providing a precise analysis of microcomedone's structure to better understand the interplay between Propionibacterium acnes and folli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 35 publications
0
46
0
4
Order By: Relevance
“…However, given the abundance of P. acnes in the human HF microbiome, it may be relevant for acne-related activities of monocyte-derived perifollicular macrophages that excessive skin colonization with certain P. acnes strains can increase TLR2-mediated monocyte secretion of IL-12 and IL-8, thus promoting an inflammatory response. [129][130][131] Retinoids and tetracyclines, two standard acne therapies, both modulate the skin microbiome, presumably causing a decrease in Propionibacteria and an increase in Staphylococci, Streptococci and overall species diversity. 132 However, a recent study has reported the opposite: a higher density of P. acnes and a decrease of Staphylococci and Enterococci in healthy controls compared with patients with acne.…”
Section: Acne Vulgarismentioning
confidence: 99%
See 1 more Smart Citation
“…However, given the abundance of P. acnes in the human HF microbiome, it may be relevant for acne-related activities of monocyte-derived perifollicular macrophages that excessive skin colonization with certain P. acnes strains can increase TLR2-mediated monocyte secretion of IL-12 and IL-8, thus promoting an inflammatory response. [129][130][131] Retinoids and tetracyclines, two standard acne therapies, both modulate the skin microbiome, presumably causing a decrease in Propionibacteria and an increase in Staphylococci, Streptococci and overall species diversity. 132 However, a recent study has reported the opposite: a higher density of P. acnes and a decrease of Staphylococci and Enterococci in healthy controls compared with patients with acne.…”
Section: Acne Vulgarismentioning
confidence: 99%
“…However, given the abundance of P. acnes in the human HF microbiome, it may be relevant for acne‐related activities of monocyte‐derived perifollicular macrophages that excessive skin colonization with certain P. acnes strains can increase TLR2‐mediated monocyte secretion of IL‐12 and IL‐8, thus promoting an inflammatory response 129–131 …”
Section: Dysbiosis Of the Human Hair Follicle Microbiome And Associated Hair Diseasesmentioning
confidence: 99%
“…C. acnes macrocolonies of more than 1,000 bacterial cells can be observed in association with the follicular epithelium of the pilosebaceous unit; they are more often present in follicles from acneic skin biopsies than in follicles of individuals with healthy skin ( Jahns et al., 2012 ). High bacterial colonization of the follicles was recently also observed in transmission electron microscopy images of microcomedones ( Josse et al., 2020 ). As C. acnes growth and proliferation in the pilosebaceous unit is considered one of the factors that contributes to the etiology of acne, we first investigated the ability of strains belonging to phylotypes I and II to associate with HaCaT keratinocytes and SZ95 sebocytes.…”
Section: Discussionmentioning
confidence: 62%
“…Another common skin disorder ripe for in vitro modelling is acne vulgaris, where genetic predispositions, hormonal changes, stress and environmental factors lead to the formation of microcomedones, [65][66][67] many of which can become inflamed. 68…”
Section: Where Org Anot Ypi C S Kin Culture S " S Hine"mentioning
confidence: 99%
“…Another common skin disorder ripe for in vitro modelling is acne vulgaris , where genetic predispositions, hormonal changes, stress and environmental factors lead to the formation of microcomedones, 65‐67 many of which can become inflamed 68 . Inflammatory microcomedones are caused by hyperseborrhoea, where fatty acid composition of sebum becomes altered, leading to accumulation of peroxidized squalene and favouring expansion of C. acnes 66,69,70 .…”
Section: Where Organotypic Skin Cultures “Shine”mentioning
confidence: 99%